Determination of Bacteriological Profile of Nosocomial Infections in Visceral Surgery at CNHU-HKM, Republic of Benin - Nicolas, Aïkou; Theodora , A. Ahoyo; Cyriaque , Degbe Sah; Amadou , Coulibaly Founzégué; Alphonse, Sezan; Patrick , Edorh A.; Lapo, R. A. (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
This study aims to identify the bacteria involved in these suppurations, to study their antibiotic resistance profiles and to review the role of the nurses taking care of these patients. Wound suppuration is the formation and accumulation of pus in the soft tissue of the wound. As a rule, the natural inflammatory reaction disappears within three to five days and later the wound heals which leads to the formation of pus, exaggeratedly prolonging the healing process and in turn leading to serious consequences. The study was conducted at the Menontin zone hospital from May 15 to June 21, 2013. Fifty-one patients of all ages and sexes with surgical and traumatic discharge wounds were sampled and 30 hand samples were taken from the nurses' hands before and after dressing. From the results obtained, 76 bacteria were identified, including 35 cocci and 41 bacilli. 29% of the bacteria found were Pseudomonas aeruginosa, 28% Staphylococcus aureus, 14% Escherichia coli and others. Hand samples of 10 bacteria were isolated including 4 Pseudomonas aeruginosa, 3Staphylococcus DNase-negative 2 Klebsiella spp and 1 Staphylococcus aureus. The strains isolated were particularly resistant to the antibiotics tested more specifically to \(β\)-lactam, Gentamycin Erythromycin and Colistin. The majority of strains have good sensitivity to ciprofloxacin and Fosfomycin. It is concluded that patients and nurses to the reality of the existence of these bacteria, the adequate intake of antibiotics preferably after an antibiotic test, hand washing and the use of appropriate sterile materials before and after any dressing.